Milly, Molly and pet day - Pittar, Gill (Milly Molly Books Gisborne, N.Z., 2002)
The Milly Molly series of books are written for children between the ages of four and eight. The stories relate the adventures of two little girls from different ethnic backgrounds and promote the acceptance of diversity and learning of life skills.